CREATION OF THE EU BANKING UNION: THE ANALYSIS OF BANKS’ POSITIONS - Vaicekauskaitė, Živilė Marija Marija (Politologija, 2016)
The study aims to explain why European banks had different positions towards establishing the EU banking union. Most of the academic publications dedicated to analyze the very recently implemented EU financial sector reforms give particular attention to explaining why different EU member states opposed the creation of a full banking union as it was proposed by the European Commission while there is a lack of academic discussions raising the question of how to explain that European banks also had different positions towards the implementation of single supervisory and resolution mechanisms. The research poses the question of how to explain different banks’ positions towards the creation of the EU banking union. While some international banks were strongly promoting the new supranational supervisory and resolution mechanisms which would be applied to the whole EU banking sector the others voiced strong opposition to the points of governance and application scope of proposed EU banking sector reforms. The overall aim of the study is to give the possible explanation of why different banks had different positions towards shaping the EU banking union. The study is based on the hypothesis that highly internationalized banks preferred greater European regulatory harmonization in the banking supervision and resolution (creating single supervisory and resolution mechanisms which would include all euro zone banks, supranational governance of banking resolution and high degree of risk sharing) while low internationalized banks preferred more the national regulatory autonomy. The research is based on the theoretical framework suggested by A. Spendzharova. The author argues that the level of bank internationalisation is an important determinant of the extent to which governments were prepared to endorse European solutions in banking supervision and resolution or prefer the national regulation. The proposed framework of the analysis has been applied to analyse countries’ positions but it has not been applied to explain banks’ preferences on the proposed elements of the EU banking union. The conducted analysis revealed that the internationalisation level alone cannot fully explain the positions of the banks on the creation of the EU banking union. The analysis of 20 biggest European banks varying from global to local banks revealed that despite being internationalized differently the majority of the banks supported the creation of the common supervisory and resolution mechanisms which would be applied to all euro zone banks. Even banks having a low internationalisation level supported the creation of the proposed EU banking union and vice versa. It can be also noted, that the majority of the banks voiced the support for the supranational governance of the single resolution mechanism but opposed the high degree of risk sharing – the creation of the ex ante resolution fund.